‘n Plantekologiese studie van die Golden Gate Hoogland Nasionale Park Clarens, Oranje-Vrystaat - Potgieter, John William (University of the Free State, 1982)
The Golden Gate Highlands National Park is situated approximately 58 km southeast of Betlehem in the Eastern Orange Free State. The Park covers approximately 4 792 ha, is situated between 1 707 and 2 800 m above sea level and is mountainous. According to the Koppen classification the study area has a warm moderate rainy climate, at least one month with mean temperature lower than 18°c and at least eight months with mean temperature higher than 1°c, coldest month higher than -3°c, dry season in winter and a mean temperature of the warmest month lower than 22°c. The mean annual rainfall of Golden Gate is 800,4 mm. The rock formations in the study area form part of the system Karoo which divides into four series; namely the Serie Dwyka, Ecca, Beaufort and Stormberg in order from the bottom to the top and therefore from the eldest to the youngest. The Serie Stormberg divides inter alia into the Etage Holkrans sandstone which is the best represented in the Park in the form of the Brandwag rock as the most well-known example. No soil survey data exist for the study area. The influence of grazing is the most important biotic factor discussed. It was observed that black wildebeest and blesbuck display territorial behaviour especially in the southern and more mountainous parts of the study area. It was further observed that a shortish grass community, namely the Catalepis gracilis-community, dominates the immediate footstamp area of such a territorium and that soil erosion of a high level occurs in such a territorium. The vegetation was surveyed and classified according to the Braun-Blanquet-technique. A total of 166 releves, representing one releve per approximate= ly 79,5 ha 2 , were set out. In each releve a floristic survey was made and a number of environmental factors such as geology, aspect, slope, height above sea level, topography, soil colour, soil texture, organic material content, adsorbed cation content, electric resistance and pH of the soil were determined. The analysis reveiled that the soil depth varies between 30 and 1 ooo+·mm in the study area. The pH of the soil varies between 4,7 and 7,8; electric resistance from 650 to 5 200 ohm, organic material content from 0,22 to 12,90%, magnesium content between 0,22 to 17,06 me/100g, sodium content from 0,01 to 0,22 me/100g, calcium content between 0,37 to 30,26 me/100g and potassium content from 0,05 to 1,39 me/100g. The data were processed and tabularized on a computer with the aid of the Braun-Blanquet-technique and 19 communities were distinguished, described and correlated with the environment. The plant communities were not classified hierarchically because of the lack of knowledge of the vegetation in the vicinity of the Park. The communities are shown in a vegetation map and are floristically and physiognomically described, while quantitative data and the relationships between the communities are shown in a sinoptic table. The plant communities are divided into two main groups : A. Communities in which Themeda triandra is poorly represented or absent. A total of 12 communities were distinguished and are characterized by the poor representation or absence of Themeda Triandra. Dominant species are Merxmuellera drakensbergensis, Andropogon appendiculatus Catalepis gracilis, Rendlia altera, Monocymbium ceresiiforme, Aristida junciformis, Eragrostis chloromelas, E. plena, Cyperus rigidifolius, Scripus burkei, Hyparhenia and Miscanthidium capense. B. Communities in which Themeda triandra is conspicuous or dominant A total of seven communities were distinguished and are characterized by the presence of Themeda triandra. Dominant species are: Helictotricon longifolium, Tristachiya leucothrix, Trachypogon spicatus Erica maesta, Elionurus, muticus, Aristida diffusa, Hyparihenia hirta and Themeda triandra. A list of all species collected in the Park is included.
Dissertation (M.Sc. (Plant Sciences (Botany))--University of the Free State, 1982
Keywords: Plant ecology; Plant physiology; Golden Gate Highlands National Park